2022
DOI: 10.1155/2022/6425133
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Heavy Metals on Gastric Tumorigenesis

Abstract: Objectives. This study aimed to observe the relationship among heavy metals concentration, microsatellite instability (MSI), and human epidermal growth factor receptor type 2 (HER2) gene amplification in gastric cancer (GC) patients. Methods. The concentrations of 18 heavy metals in the plasma of GC patients and healthy controls were measured by inductive coupled plasma emission spectrometry (ICP-MS). MSI detection was conducted by detecting 5 microsatellite repeat markers by PCR analysis. HER2 gene amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Expression. To confirm the mechanism through which chronic Tl acetate exposure induces malignant transformation, we first observed increased levels of m 6 A modification with an increase in cell passage number (Figure 6A,B). Chronic Tl acetate exposure induced a significant increase in the mRNA and protein levels of ATP13A3 with an increase in cell passage number (Supplementary Figure 14A,B).…”
Section: Chronic Tl Acetate Exposure Increases the Level Of N 6 -Meth...mentioning
confidence: 87%
See 4 more Smart Citations
“…Expression. To confirm the mechanism through which chronic Tl acetate exposure induces malignant transformation, we first observed increased levels of m 6 A modification with an increase in cell passage number (Figure 6A,B). Chronic Tl acetate exposure induced a significant increase in the mRNA and protein levels of ATP13A3 with an increase in cell passage number (Supplementary Figure 14A,B).…”
Section: Chronic Tl Acetate Exposure Increases the Level Of N 6 -Meth...mentioning
confidence: 87%
“…In addition, treating the transformed cells with a global methylation inhibitor [3-deazaadenosine (DAA)] substantially reduced the m 6 6K and Supplementary Figure 14D). Thus, our data demonstrated that an increase in the m 6 A writer complex (METTL3 and METTL14) and a decrease in the eraser ALKBH5 induced by chronic Tl acetate exposure in transformed cells promote increases in the m 6 A modification and expression levels of ATP13A3.…”
Section: Chronic Tl Acetate Exposure Increases the Level Of N 6 -Meth...mentioning
confidence: 99%
See 3 more Smart Citations